Lenalidomide as immune adjuvant to a dendritic cell vaccine in chronic lymphocytic leukemia patients. (22nd May 2018) - Palma, Marzia; Hansson, Lotta; Mulder, Tom A.; Adamson, Lars; Näsman‐Glaser, Barbro; Eriksson, Ingrid; Heimersson, Kia; Ryblom, Harriet; Mozaffari, Fariba; Svensson, Ann; Gentilcore, Giusy; Österborg, Anders; et al.
Abstract: Objectives: We previously showed that immunization with ex vivo‐ generated autologous dendritic cells loaded with apoptotic tumor cells (Apo‐DC) potentiated tumor‐specific immunity in chronic lymphocytic leukemia (CLL) patients. Here, we evaluated safety and immunogenicity of Apo‐DC in combination with lenalidomide, granulocyte‐macrophage colony‐stimulating factor (GM‐CSF), and low‐dose cyclophosphamide (CTX). Methods: Ten previously untreated patients with slowly progressing CLL received 5 Apo‐DC vaccinations and lenalidomide orally for 24 weeks either alone (cohort I, n = 5) or together with subcutaneous GM‐CSF and intravenous CTX (cohort II, n = 5). Tumor‐specific T‐cell responses were measured by proliferation and IFN‐γ ELISPOT assays. Immune monitoring was performed by flow cytometry. Results: Dose‐limiting toxicity was observed in 3/10 patients, 2 in cohort I and one in cohort II. One patient developed autoimmune hemolytic anemia and another grade 4 thrombocytopenia. Vaccine‐induced immune responses were seen in 5/5 and 4/5 patients in cohort I and II, respectively. The expression of immune checkpoints on T cells did not change significantly. Conclusions: Lenalidomide alone or in combination with GM‐CSF and low‐dose CTX as immune adjuvant to the Apo‐DC vaccine elicited tumor‐specific T‐cell responses in CLL patients. However, unexpected toxicity was observed and caution is suggested in further exploring this drug as immune adjuvant in CLL.